(untitled) (Journal of Oriental Studies, 2022)
This article provides a comparison of typical properties of the principal features of the main and auxiliary verbs and a study of the tense categories and moods of the historical Mamluk-Kipchak language in comparison with the modern Kazakh language considering such well-known written sources in the Mamluk-Kipchak language of XIIІ-XV centuries as “Kitab al-Idrak Li-Lisan Al- Atrak”, “Kitab majmua tirjuman turki ua ajami ua muguli ua farsi”, “Kitab ad-durra al-mudiyya fi al-luga”, At-turkiya ala at-tamam ua al-kamal” and “Al-Qawanin al-kulliya lidabt al-lugat at- turkiya”. In this regard, descriptions of the mentioned written sources were given first, and a brief overview of special and general studies on the study of the historical Mamluk-Kipchak language is also provided. The comparative study showed that the main verbs and auxiliary verbs in the Mamluk- Kipchak language and the modern Kazakh language have structural and semantic similarities, as well grammatical similarity in terms of tense and mood. The definition of the process of lexical and grammatical continuity between the historical Mamluk-Kipchak language and the modern Kazakh language, which is the basis of the article, has particular importance from the point of view of studying the historical development of the Kazakh language. Key words: Mamluk-Kipchak language, manuscript, Kazakh language, verb, tense category